Pendekatan Edukatif Guru untuk Mengatasi Tantangan Anak Hiperaktif di TK Dharma Wanita Desa Sempu Ngebel Ponorogo - Ahmad Zainal Abidin; Suci Midsyahri Azizah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service aims to describe how teachers identify hyperactive children, strategies used in dealing with hyperactive children's behavior, and the impact on hyperactive children at Dharma Wanita Kindergarten, Sempu Ngebel Village, Ponorogo. The community service method uses Asset, Based, Community, and Development (ABCD) with data collection techniques through observation, interviews, and documentation. The results of the community service show that the teacher's educational approach to dealing with hyperactive children implemented includes providing motivation, individual guidance, special attention, placing children in the front position, the use of fun learning methods, and educational media such as puzzle games. The impact on hyperactive children includes limited understanding of children's special needs, lack of resources and training, and suboptimal parental support. This community service concludes that the role of teachers is very important in creating a conducive learning environment for hyperactive children, with synergistic support from schools and parents. It is recommended that teachers improve their competencies through inclusive learning training, while schools and parents strengthen cooperation for the successful management of hyperactive children.